Minoxidil poisoning presenting as acute coronary syndrome: a rare case scenario - Panchal, Shrikant Kalyanrao; Mudgalkar, Nikhil; Reddy, K. Ravinder (International Journal of Research in Medical Sciences, 2017)
We present a case of severe minoxidil poisoning (3000 mg) with resultant severe hypotension, tachycardia and subendocardial ischemia initially treated crystalloid, dopamine, aspirin, clopidogrel on the lines of acute coronary syndrome with partial haemodynamic improvement. After getting the history of minoxidil poisoning, the patient was treated with bolus doses of norepinephrine, and norepinephrine infusion, resulting in resolution of hypertension, tachycardia and reversal of ischemia. Topical minoxidil is commonly used agent for male pattern baldness. It also has got antihypertensive action when ingested, acute coronary syndrome and compensatory tachycardia with successful management with norepinephrine bolus and infusion.